Shakespeare and gender in practice - Power, Terri (Shakespeare in practice, 2016)
"This book explores theoretical and practical approaches to performing gender in contemporary Shakespeare productions. It focuses on contemporary practice, looking at how it is responding to a new cultural politics of gender and creating a critical language for understanding the performing of gender in the staging of Shakespeare's plays"--